2015
DOI: 10.1038/onc.2015.371
|View full text |Cite
|
Sign up to set email alerts
|

Somatic human ZBTB7A zinc finger mutations promote cancer progression

Abstract: We recently reported that ZBTB7A is a bona fide transcription repressor of key glycolytic genes and its downregulation in human cancer contributes to tumor metabolism. As reduced expression of ZBTB7A is found only in a subset of human cancers, we explored alternative mechanisms of its inactivation by mining human cancer genome databases. We discovered recurrent somatic mutations of ZBTB7A in multiple types of human cancers with a marked enrichment of mutations within the zinc finger domain. Functional characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…1a), as already described in other readouts [1]. Despite a previous report in the context of colon cancer suggesting that ZBTB7A zinc finger mutations act in a dominant negative manner [22], we could not find any evidence for this effect in our models, even when the expression of the R402C mutant was slightly higher than the control (Fig. 1e).…”
Section: Zbtb7a Causes Cell Cycle Arrestsupporting
confidence: 59%
“…1a), as already described in other readouts [1]. Despite a previous report in the context of colon cancer suggesting that ZBTB7A zinc finger mutations act in a dominant negative manner [22], we could not find any evidence for this effect in our models, even when the expression of the R402C mutant was slightly higher than the control (Fig. 1e).…”
Section: Zbtb7a Causes Cell Cycle Arrestsupporting
confidence: 59%
“…Overexpression of Zbtb 7a in murine prostate epithelium did not result in neoplastic transformation; unexpectedly, Zbtb7a inactivation lead to the acceleration of Pten-driven prostate tumorigenesis 20 . Recently, somatic zinc-finger mutations of ZBTB7A were found at low frequencies (<5%) in a variety of solid cancers suggesting a common mechanism across tumour entities 21 . In fact, the de-repression of glycolytic genes upon deletion or mutation of ZBTB7A 10 21 might underlie the loss of anti-proliferative properties that we observed for ZBTB7A mutants A175fs and R402C in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…These values are significantly higher compared to that of RACER network with 12 and 9 degrees. Previous studies [50,51] have shown that ZBTB7A functions as a transcriptional suppressor. ZBTB7A was also proven to play a critical role in AML as a transcription factor in [52].…”
Section: Results For Dream4mentioning
confidence: 95%